2013
DOI: 10.1542/peds.2012-3868
|View full text |Cite
|
Sign up to set email alerts
|

Using Otoacoustic Emissions to Screen Young Children for Hearing Loss in Primary Care Settings

Abstract: WHAT'S KNOWN ON THIS SUBJECT: The incidence of permanent hearing loss doubles between birth and school age. Otoacoustic emissions screening has been used successfully in early childhood educational settings to identify children with losses not found through newborn screening. WHAT THIS STUDY ADDS:Using otoacoustic emissions to screen the hearing of young children during routine health care visits is feasible and can lead to the identification of permanent hearing loss overlooked by providers relying solely on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 10 publications
1
10
0
1
Order By: Relevance
“…Authors who performed the DPOAE in 105 children found that 5.37% presented alterations 28 . DPOAE was also performed in 846 children from another study, in which 96% of the subjects passed the hearing screening 29 , similar to the data found in the present study.…”
supporting
confidence: 86%
“…Authors who performed the DPOAE in 105 children found that 5.37% presented alterations 28 . DPOAE was also performed in 846 children from another study, in which 96% of the subjects passed the hearing screening 29 , similar to the data found in the present study.…”
supporting
confidence: 86%
“…In a number of studies focusing on ototoxicity in children, otoacoustic emissions were applied for monitoring ototoxicity . Currently, otoacoustic emissions are widely used in newborn hearing screening programs and are validated by professional organizations as a reliable and objective tool …”
Section: Discussionmentioning
confidence: 99%
“…With the introduction of portable and handheld equipment, tympanometry has become more feasible for a primary care setting. Future proofing of audiology equipment requires provision for otoacoustic emissions technology, initially used for newborn hearing screening but shown to have potential in small children 330 and the aged. Acoustic reflectometry is a technique based on a sonar that enables the diagnosis of middle ear effusion.…”
Section: Equipmentmentioning
confidence: 99%